(untitled) (Computer systems and information technologies, 2022)
The constant growth of digital information and online services highlights the need to protect the rights of people with disabilities in terms of web accessibility. Despite EU regulations aimed at harmonizing this process, some problems still remain unsolved. This article sheds light on legal documents protecting the rights of people with disabilities regarding web accessibility. The conducted profound analysis of abundant research and applied papers showed the lack of systematization of accessibility testing standards. The authors disclosed modern approaches to testing the accessibility of web applications depending on the special needs of users and elaborated the checklist for testing the accessibility of web-applications.